A Highly Compact Split Ring Resonator-Based Rectangular Dielectric Resonator Antenna With Multiband Characterization - Shahid Khan; Owais Khan; Kiran Raheel; Syed Ahson Ali Shah; Bilal Tariq Malik; Salahuddin Khan; Neelam Gohar; Slawomir Koziel (IEEE Access)
This work encompasses a novel highly compact Split Ring Resonator (SRR) based quad-band Dielectric Resonator Antenna (DRA) for 4G and 5G applications. The proposed antenna comprises of an extended rectangular feedline and a rectangular DR in combination with two SRRs. The DRA uses the extended rectangular microstrip feedline for providing better impedance matching and enhanced performance. Remarkably, the introduction of SRRs on either side of the feedline enables the DRA to resonate at four distinct frequency bands, i.e., 1.62 GHz, 3.03 GHz and 4.7 GHz and 6.56 GHz respectively. The two lower operating bands with narrow band response are due to SRRs while two upper bands with wide band characteristics are due to rectangular DR. The simulated performance of the rectangular DRA is validated through measurements, performed on a fabricated prototype. At the corresponding resonance frequencies, the suggested design exhibits −10 dB impedance bandwidths of 9.2%, 5%, 8.3%, and 5.6%. With a notable peak gain of 2.3 dBi and an efficiency of 93%, the suggested design has excellent radiation pattern stability. To the best of authors knowledge, this is the first design where SRRs are incorporated with rectangular DR to achieve multiband operations. The simulated and measured findings show a strong agreement, highlighting the SRR-based DRA appropriateness for multiband wireless applications (such as satellite television, radio astronomy, Bluetooth, WiFi, and 6G), while demonstrating its significant contribution to the field.